Flexible all-solid-state hierarchical NiCo2O4/porous graphene paper asymmetric supercapacitors with an exceptional combination of electrochemical properties. (April 2015) - Gao, Zan; Yang, Wanlu; Wang, Jun; Song, Ningning; Li, Xiaodong
Abstract: Two nanostructured electrodes were fabricated and used to construct flexible high performance supercapacitors. Hierarchical NiCo2 O4 nanostructures (with airy organdy NiCo2 O4 nanosheets on vertical NiCo2 O4 nanoarrays) were grown on flexible carbon cloth by a facile template-free method while three dimensional (3D) porous graphene papers (PGP) with scaffold-like microstructure were fabricated by freeze-drying. The hierarchical NiCo2 O4 /carbon cloth (NiCo2 O4 /CC) and PGP electrodes achieved the maximum specific capacitance of 1768 (based on the mass of NiCo2 O4 ) and 151 F g −1, respectively. The NiCo2 O4 /CC (as the positive electrode), PGP (as the negative electrode), and PVA–LiOH gel (as both the solid state electrolyte and separator) were assembled into flexible all-solid-state (NiCo2 O4 /CC//PGP) asymmetric supercapacitor with an exceptional combination of electrochemical properties in terms of working potential (1.8 V), maxmum energy density (60.9 W h kg −1 ), maxmium power density (11.36 kW kg −1 ), and cycling stability (96.8% capacitance retention ratio over 5000 cycles under mechanical bending). Graphical abstract: Highlights: Nanostructured NiCo2 O4 nanosheets/carbon cloth (NiCo2 O4 /CC) positive material was synthesized via a facile hydrothermal method. Free-standing 3D porous graphene paper (PGP) was chosen as negative electrode materials. Solid-state asymmetric NiCo2 O4 /CC//PGP supercapacitor exhibits an exceptional combination of electrochemical properties.